Clinical Characteristics of Cancer Patients With COVID-19: A Retrospective Multicentric Study in 19 Hospitals Within Hubei, China - Guo, Deliang; Wang, Haitao; Zhu, Qian; Yuan, Yufeng (Frontiers in Medicine, 2021)
Abstract Objective: This study aimed to determine the association between prognosis of COVID-19 patients with and without cancer. Moreover, we compared the prognosis of cancer patients subjected to anti-tumor therapy with those who have not undergone anti-tumor therapy in the past six months. Methods and results: A total of 7926 adult patients with COVID-19 were retrospectively enrolled in Hubei Province，China between December 31, 2019 and February 20, 2020. 277 cancer patients (cancer group, median age 64 [IQR 56-70] years; 50.90% male) and 7649 non-cancer patients were identified (non-cancer group, median age 55 [IQR 42-64] years; 48.19% male). The mortality rate was lower in the non-cancer group compared to the cancer group (4.50% vs. 9.03%; P＜0.001). The duration between onset and admission shorter in the cancer group (Days, 9 [IQR 5-18]) compared to the non-cancer group (Days, 10; [IQR 6-19]; P=0.036). ICU occupancy was higher in the cancer group (n[%], 30[10.83%]) than in the non-cancer group(n[%], 314[4.11%]). In reviewing the anti-tumor therapy, data from 277 selected cancer patients were obtained out of which 74 patients had undergone anti-tumor therapy (mean age 65 [IQR 51-67] years; 45.95% male), 203 had not undergone anti-tumor therapy (non-anti-tumor therapy group, mean age 63 [IQR 53-75] years; 49.75% male) in the past 6 months. The mortality rate for the anti-tumor therapy group and the non-anti-tumor therapy group was similar (9.46% vs. 8.87%; P=0.879). Conclusion: The mortality rate was higher in COVID-19 patients with cancer compared to those without cancer. Moreover, anti-tumor therapy in the past 6 months did not worsen the prognosis of cancer patients with COVID-19.